Mezi „Pryč od Říma!“ a „Modem vivendi“: Z osudů katolické církve v Československu za první republiky - Kružíková, Jana (Lidé města, 2005)
Since the beginning of the 20th century, in religion, as well as in other sectors of social life in the Czechoslovak Republic, the influence of secularization, liberalization, and modernization started to manifest itself. The impact was following: 1) decline in numbers of Catholics, 2) strengthening the influence of Protestant Churches, and 3) attempts to reform the Roman-Catholic Church and calls for its modernization. Now, we gradually pay attention to these phenomena. In 1910 (during the last census undertaken in the Austrian Monarchy), 90 % of Czechs declared themselves as Catholics. In 1921 (during the first Czechoslovak census), their numbers decreased to 82 %. In 1930, only 78% of inhabitants declared to be Roman Catholics. After 1918, some of the former Catholic worshippers went over to the Protestant Churches, some of them joined the newly formed Czechoslovak Church and majority was without denomination. During the 1930 census, persons “without denomination” composed the second largest group of inhabitants as classified by their denomination - approximately 8%. There were two major waves of leaving the Roman Catholic Church: 1) following creation of the Czechoslovak Republic in 1918, 2) in 1920, in connection with unsuccessful attempts to reform the Church. Since inhabitants of Czechoslovakia connected the Catholic Church with the Habsburg Monarchy (the idea of a union of throne and alter was common - for example the slogan: “We made a clean break with Vienna, we shall do the same with Rome” or “May good Czech be - or remain - Catholic?”). They considered leaving the Church as a demonstration of independence of the new Czechoslovak Republic; as weakening of Church’s influence on life in the new state.